A Study on the Impact of Yoga on Daily Yoga Practitioners (Madhyabindu Journal, 2021)
This study identifies the reasons for practicing and the impact of yoga in yoga practitioners among different yoga centers in Kawasoti Nawalpur. Yoga is a part of mainstream culture today, with major medical centers, community healthcare centers, and neighborhood yoga studios offering yoga as a mind-body practice to support health and healing. The significance of this research is to study the physical and mental impacts of yoga on daily yoga practitioners at yoga centers in Kawasoti Nawalpur. For this, the researcher went to various yoga centers and met the people who practice daily yoga, and inquired about the causes and impact of yoga. This study shows that the main reasons for practicing yoga among yoga practitioners were; backache, joint pain, or muscular pain (33.33 percent) and abdominal problems including gastritis and uterine problem (38.88 percent). Yoga practitioners experienced the positive effects and achievements of yoga are; backache, joint pain or muscular pain (29.16 percent) improve, and abdominal problem including gastritis and uterine problem (50.00 percent) improve. So, after identifying the positive impacts of yoga, the researcher suggests that more emphasis or public awareness can be given to yoga practice for minimizing chronic health problems. The findings will help the individual, teachers, scholars, career, and counseling centers.